Analisis Semiotika Roland Barthes pada Masjid Keraton Buton di Kota Baubau, Sulawesi Tenggara - Nurul Fitriana Bahri (JURNAL RUPA, 2019)
Baubau is one of the cities that has a lot of potential in local culture, located within Southeast Sulawesi Province of Buton Island. Fort of Keraton Buton is one of the local cultures that has become Baubau's identity as well as proudly icon of its people and Southeast Sulawesi in general. Inside of the fort's complex stands a mosque that is a legacy from Buton Sultanate. This mosque is known as Masjid Keraton Buton. Masjid Keraton Buton is an architectural work that has become the united source of ideas from every social field, including how religion belief was interpreted and understood for the people's interest. It's difficult to divide its architectural presence to two form of culture that precedes its birth. One is social system and the other is idea complexity. Roland Barthes semiotic analysis of shape, construction, space and color on Masjid Keraton Buton is conducted in this essay. Semiotic is a knowledge that learns about signs, how it is functioned and the meaning it's produced. Roland Bathes is one of the figures of semiotic, he argued semiotic is part of the linguistic. According to him, language is a sign system that reflects assumptions from one certain community in a certain time. This matter revealed an idea and is an element that shaped from signs and included inside a structure.